Introduction: Sustainability in the coastal zone - Heidkamp, C.P.; Morrissey, J. (Towards Coast. Resil. and Sustainability, 2018)
Coastal areas provide many co-benefits associated with their natural infrastructure, facilitating activities such as fishing, industry, tourism and transportation, for instance (Barragán & de Andrés, 2015; Sutton-Grier, Wowk & Bamford, 2015). Despite occupying a relatively small percentage of the Earth's land surface, the value of the ecosystems’ services of coastal areas is more than one-third of the total for the globe (Barbier et al., 2011; Barragán & de Andrés, 2015). However, while the goods and services provided by coastal ecosystems are essential for economic and social well-being (Mavrommati, Bithas & Panayiotidis, 2013), coastal ecosystems are increasingly at risk. As a direct result of intensive resource use and of concentrations of population, coastal ecosystems increasingly demonstrate direct and adverse impacts of human activities (Swaney et al., 2012). Increasing population growth, movement of populations towards the coast and the increase in coastal development have led to an increase in pressure on, and degradation of, coastal ecosystems (Duxbury & Dickinson, 2007). For large coastal cities, interactions between human activities and coastal systems are intensified due to population density effects and associated economic activities (Mavrommati et al., 2013). In many parts of the world, coastal natural habitats are declining and overexploited coastal resources are dwindling, with associated impacts on ecosystems and on the livelihoods dependent on these (Mee, 2012). © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Coastal development; Coastal ecosystems; Coastal resources; Coastal zones; Economic activities; Economics; Ecosystems; Increase in pressure; Population densities; Population growth; Population statistics; Social well-being; dept.egm

Robust quantification of fish early life CO2 sensitivities via serial experimentation - Baumann, Hannes; Cross, Emma L.; Murray, Chris S. (Biology Letters, 2018)
Keywords: dept.egm; peer-reviewed

Data and policy scale mismatch in coastal systems : The potential of μUAS as new tools for monitoring coastal resilience - Graves, Scott M. (Towards Coastal Resilience and Sustainability, 2018)
An important challenge in monitoring, planning and evaluating coastal saltmarsh resources in the face of predicted sea level rise (SLR) using numerical
Keywords: 3D modeling; Antennas; Coastal systems; Flight planning; Model results; Numerical models; Remotely sensed data; Scale mismatches; Sea level; Sea level rise; Structure from motion; Unmanned aerial systems; Unmanned aerial vehicles (UAV); Wetlands; dept.egm

Conclusion: Outlook for coastal transitions - Heidkamp, C. Patrick; Morrissey, John; Morrissey, John (Towards Coastal Resilience and Sustainability, 2018)
Globally, rapid demographic change of coastal urban agglomerations, the speed of urbanisation over time, the overall impact of coastal space occupation as well
Keywords: Climate change; Coastal ecosystems; Coastal zones; Demographic changes; Economics; Ecosystem services; Ecosystems; Energy availability; Flood control; Impervious surface; Long term process; Sea level; Topography; Urban agglomerations; Urban development; Urban growth; dept.egm

Harnessing place attachment for local climate mitigation? Hypothesising connections between broadening representations of place and readiness for change - Upham, Paul; Johansen, Katinka; Bögel, Paula Maria; Axon, Stephen; Garard, Jennifer; Carney, Sebastian (Local Environment, 2018)
Keywords: dept.egm; peer-reviewed

The human factor: Classification of European community-based behaviour change initiatives - Axon, Stephen; Morrissey, John; Aiesha, Rosita; Hillman, Joanne; Revez, Alexandra; Lennon, Breffní; Salel, Mathieu; Dunphy, Niall; Boo, Eva (Journal of Cleaner Production, 2018)
Behaviour, practices and culture constitute a powerful human factor in the energy system; in particular the interactions between technologies, practices and norms lock individuals in to certain patterns of (often inefficient) energy use. Consequently, behaviour change has gained traction amongst policy makers as a key area of intervention given the impact energy-related behaviours have on climate change. Given the increasing emphasis within policy perspectives in the European Union, it is surprising that a gap in understanding of the success factors of behaviour change initiatives remains. This paper addresses this gap by identifying and characterising behaviour change initiatives across five European countries (the UK, Ireland, France, Italy, and Spain). The paper provides insights into the success factors and commonly encountered barriers to behaviour change initiatives. Initiatives are classified into 6 broad categories (community-based interventions; information and awareness based interventions; eco-districts; show-case events; energy switching; and smart-technology focused interventions). The results suggest that there are significant knowledge gaps between what is known to work to engage individuals in behavioural change and what is currently being applied in practice. An over-reliance on education and awareness-raising projects is evident, illustrating that such projects do not sufficiently aim for sustained behavioural changes. A dearth of projects incorporating fiscal measures, regulations or legislation to drive behaviour change reflects reluctance on behalf of decision-makers to engage widely with diverse approaches to foster lifestyle change. This paper contributes understandings of the different models and delivery tools employed to change energy-related behaviours; insights into the critical success factors that underpin best practice and the barriers to action; and a `what works in practice' overview of the meaningful approaches to change behaviour. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Behaviour change; Behaviour changes; Binary alloys; Climate change; Decision making; Energy; Europe; Human engineering; Interventions; Laws and legislation; Potassium alloys; Practices; Sustainability; Sustainable development; Uranium alloys; dept.egm; peer-reviewed

A 120-year record of resilience to environmental change in brachiopods - Cross, Emma L.; Harper, Elizabeth M.; Peck, Lloyd S. (Global Change Biology, 2018)
Keywords: dept.egm; peer-reviewed

Social enterprise as a potential niche innovation breakout for low carbon transition - Hillman, Joanne; Axon, Stephen; Morrissey, John (Energy Policy, 2018)
While there is growing consensus that human behaviours need to change to a more sustainable paradigm, community driven approaches, such as social enterprise, have yet to be explored as serious instruments of sustainability transition. Social enterprises sit within the third sector of the economy, typically where market or governmental failures exist in the provision of social welfare, and have increasingly become a key driver of social progress. The autonomous nature of the social-economic model applied by such organisations can represent a viable means to reduce state social welfare dependence, and is a proven model for social change. The capability of social enterprises to create both social and economic value is considered a `win-win'. Yet there are clear potentials for social enterprise models to be more extensively applied to address contemporary ecological challenges of neo-liberal market economies, moving towards `win-win-win' outcomes across social, economic and ecological domains. This paper investigates the value of social enterprises as drivers of low-carbon transition at the community level, with an emphasis on the energy sector. Evidence from seven organisations in the UK is presented and a socio-technical transitions conceptual framework is applied to analyse these social enterprise operations as a form of social innovation.
Keywords: Behavioral research; Carbon; Commerce; Conceptual frameworks; Ecology; Energy; Innovation; Low-carbon transitions; Social Enterprise; Social enterprise; Social innovations; Socio-technical regimes; Socio-technical transitions; Sustainability Transitions; Sustainability transition; Sustainable development; United Kingdom; carbon; carbon emission; dept.egm; emission control; environmental economics; innovation; sustainability; welfare provision

Examining historical land management and current urban forest health - Massa, Amanda; Zavar, Elyse; Lavy, Brendan L.; Graves, Scott M. (Northeastern Geographer, 2018)
Urban forests can serve as valuable oases for birds and other wildlife in densely-populated urban and suburban areas with proper management. This study analyzes forest health and habitat availability of a publically-owned urban forest in West Haven, Connecticut. During the first half of the twentieth-century, this urban forest was privately-owned and primarily managed as an orchard and meadow for grazing horses. By the mid-twentieth-century, farming dwindled on the land and vegetation overtook the property. Today, this closed-canopy forest, with access to both freshwater streams and marshlands, provides habitat to a variety of native and invasive plant and animal species. By identifying the forest species and characteristics of the six hectare Cove River Historic Site (CRHS) urban forest, this study serves as the first forest inventory and provides a baseline dataset to help manage an ecologically important urban forest. Additionally, we identified bird habitat opportunities and bird species at the property. This study considers both the historic land management practices of this site in tandem with present-day forest health and animal activity to understand how this fragmented forest contributes to local biodiversity. The results indicate that this property, located within the urban environment of the central Connecticut coastline, offers varied habitats and food sources for many resident and migratory bird species, as well as wildlife including foxes.
Keywords: BIRD habitats; FOREST health; LAND management; MIGRATORY birds; URBAN forestry; bird habitat; conservation; dept.egm; invasive species; land management; peer-reviewed; urban forestry; ⛔ No DOI found

A transitions perspective on coastal sustainability - Morrissey, John; Heidkamp, C. Patrick (Towards coastal resilience and sustainability, 2018)
This chapter presents a review of the multi-scalar complexities of coastal sustainability challenges. It focuses on three discrete vignettes of innovation, which range from a novel and emerging innovation, a maturing innovation and an innovation which has become mainstream and part of the prevailing socio-technical regime. The first vignette focuses on 3D ocean farming off the coast of Connecticut in Long Island Sound, USA, as an example of an emerging niche-level innovation. The second vignette discusses the development of offshore wind energy capacity in Liverpool Bay, UK as an example of a socio-technical innovation that is more mature. The final vignette discusses containerisation as an example of a fully matured socio-technological change. The chapter argues that a spatial perspective on transition is critical to adequately account for uneven development processes and to recognise the heterogeneity of different places in terms of potential for low-carbon transition. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Barium alloys; Coastal sustainability; Development process; Liverpool bays; Low-carbon transitions; Off-shore wind energy; Offshore oil well production; Socio-technical regimes; Sociotechnical; Sustainable development; Technological change; Wind power; dept.egm

Towards a just assessment tool for identifying food deserts using a space-time economic model. - Ritchie, Michelle; Heidkamp, C. Patrick; Frazier, Tim (Northeastern Geographer, 2018)
Keywords: dept.egm; peer-reviewed; ⛔ No DOI found

Coastal sediment management as a response to intensifying storms and sea level rise: A case study - Tait, James; Orlowski, Ryan; Brewer, Jessica; Miller, Matthew D (Towards coastal resilience and sustainability, 2018)
In a period of rising sea levels and intensifying storms, enhancing coastal resilience and finding sustainable ways of living with the coast have become necessary concerns. Investigations of storm wave damage to coastal structures on the Connecticut shoreline during Hurricane Irene and Superstorm Sandy revealed that the width and height of frontal beaches were the most common denominator in mitigating the damages. One of the major problems, particularly for a state like Connecticut that has a highly developed coastline with systematically eroding beaches, is that the cost of beach nourishment projects is not only high but is increasing rapidly. The cost of beach nourishment at Prospect Beach in the town of West Haven is instructive. However, considering the importance of beaches and the costs of replenishment, rethinking Environmental Protection policies in favour of instituting regional and local sediment management practices may be in order. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Beach nourishment; Beach nourishment projects; Beaches; Coastal sediments; Coastal structures; Common denominators; Sea level; Sea level rise; Sediment management; Shore protection; Storm waves; Storms; Sustainable development; dept.egm

The human geographies of coastal sustainability transitions - Axon, Stephen (Towards coastal resilience and sustainability, 2018)
This chapter provides an overview of public engagement, its importance and effective approaches to meaningfully involve the public with coastal sustainability transitions. It presents two case studies, Guernsey, British Channel Islands and Cape Wind, Massachusetts. These illustrate how concepts of identity, marginality and engagement are essential to the development of coastal sustainability transitions. As the case study of Guernsey outlines, coastal sustainability transition-related public engagement should seek to enhance the local distinctiveness of coastal areas and 'fit within the wider narrative of place identity and how individuals feel attached to places that are ascribed with specific meanings'. Furthermore, as the case study of Cape Wind illustrates, coastal sustainability transitions need to connect with local communities in terms of addressing immediate social and economic concerns. Therefore, as a research agenda, the human geographies of coastal sustainability transitions can be of substantial value to the practical application of sustainability. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Case-studies; Coastal sustainability; Economic concerns; Effective approaches; Local community; Massachusetts; Public engagement; Research agenda; Sustainable development; dept.egm